Mindfulness, social evaluation anxiety, and self-regulation: exploring their association on impulsive behavior among athletes - Zhong, Zhangyi; Jiang, Hongyu; Wang, Huilin; Liu, Yang (Frontiers in Psychiatry, 2024)
Introduction: Athletes, due to frequent physical interactions in competitive sports, are prone to impulsive behavior. Impulsive behavior is a prevalent psychological factor in sports, often leading to performance-affecting errors. This cross-sectional survey investigated the relationship between mindfulness and athletes’ impulsive behavior. Methods: We sampled 403 athletes from youth training centers, universities, sports academies, and clubs in China using convenience and snowball sampling. Using AMOS v23, we analyzed the data with a structural equation model. Results: Our structural equation model confirmed that mindfulness and self-regulation inversely correlate with impulsive behavior, while social evaluation anxiety positively correlates with impulsive behavior. Furthermore, self-regulation and social evaluation anxiety serve as intermediaries in the link between mindfulness and impulsive behavior. Discussion: This research suggests introducing mindfulness meditation practices in competitive settings to improve athletes’ social evaluation anxiety and enhance their self-regulation abilities, thereby boosting their psychological health and curbing impulsive behavior.